PENGEMBANGAN APLIKASI TEST KEMAMPUAN PADA PENERIMAAN MAHASISWA BARU BERBASIS SMARTPHONE - Mahdianta Pandia; Pengarapenta Bangun (UPPM, 2016)
Android is an operating system for mobile phones based on Linux. Android provides an open platform for developers through a wide range of mobile devices to create an application for use. Android is a computer code that open (open source) can be distributed so that developers new applications can make it. In this paper, the authors take advantage of Android for the design of an application that is used in the process Ability test STMIK Kristen Neumann Indonesia. With this application Ability Test students may have the ability and the speed of thought testing. Students acquire knowledge and the ability to manage the logic, concentration, memory and the ability in arithmetic. Application Ability Test is knowing also beneficial for Admin and lecturer, on what skills in new students to undergo the process of teaching in Christian Neumann STMIK Indonesia. This application is also very easy to use by all circles.